ANTIBACTERIAL ACTIVITY OF AWAR-AWAR LEAVES (Ficus septica Burm f) AGAINST Staphylococcus aureus ATCC 29523 AND Escherichia coli ATCC 35218 - Khusnuryani, Arifah; Fuad, Zainatul (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2015)
This research was conducted to observe the activity of ethanol extract of Awar-awar (Ficus septica Burm f) leaves as antibacterial against Staphylococcus aureus ATCC 29523 and Escherichia coli ATCC 35218 based on the formation of clear zone and analysis of cell leak. The result showed that ethanol extract of awar-awar leaves performed antibacterial activity against S. aureus ATCC 29523 and E. coli ATCC 35218. Based on the clear zone diamter, that antibacerial activity was categorized as medium. The analysis of cell leak using spectrophotometer at λ 260 nm and 280 nm did not indicate that ethanol extract of awar-awar leaves can cause cell leak on S. aureus ATCC 29523 and E. coli ATCC 35218.